Gender disparities in Africa’s labor markets: a cross-country comparison using standardized survey data - (:unkn) unknown (My University, 2010)
Gender inequality in the labor market remains a pressing problem in contemporary Africa. Although there are large ariations across countries in male and female labor market outcomes, evidence shows that, in several countries of the region, women are less likely to be in paid jobs, and those that are employed are disproportionately concentrated in informal and precarious employment and paid substantially less than men (for example, Appleton, Hoddinott, and Krishnan 1999; Bigsten and Horton 1997; Brilleau, Roubaud, and Torelli 2004; ECA 2005; Glick and Roubaud 2004; ILO 2002; Lachaud 1997). While the lack of decent employment for both men and women is at the heart of the poverty battle in Africa, the fact that women experience greater diffi culties in the labor market is an additional concern and a specifi c poverty challenge. Women’s employment and earnings are essential in the fi ght against poverty, not only because of the direct contribution they make to household welfare, but also because such employment provides personal power for women in making family decisions and redirecting household spending on essential needs, especially in favor of children’s health and education (UNICEF 1999). Supporting employment for women is also instrumental in securing initial investment in girls’ education. Assessing and comparing women’s disadvantages in African labor markets remains a challenge, however. In-depth comparative analyses are lacking, largely because reliable and comparable comprehensive data have been scant and have the following limitations. First, when centralized databases do exist, they typically break down only a few basic labor market indicators by gender, whichyields incomplete information on the relative situations of men and women and does not allow comparison between indicators. A further problem is thatreported labor market indicators by gender are often not comparable across countries because they refer to different survey instrumen
Keywords: African Research